Climate change in a changing world: Socio-economic and technological transitions, regulatory frameworks and trends on global greenhouse gas emissions from EDGAR v.5.0. (September 2021) - Oreggioni, Gabriel David; Monforti Ferraio, Fabio; Crippa, Monica; Muntean, Marilena; Schaaf, Edwin; Guizzardi, Diego; Solazzo, Efisio; Duerr, Marlene; Perry, Miles; Vignati, Elisabetta
Highlights: The EDGAR dataset provides decades-long time series of GHG emissions for all world countries. The EDGAR V5.0 updates CO2 emissions data to 2018 and non-CO2 to 2015. EDGAR shows an overall upward trend for global GHG emissions. A detailed overview of emission trends and features is provided by gas, by activity sector and by geographical areas. Abstract: Over the last three decades, socio-economic, demographic and technological transitions have been witnessed throughout the world, modifying both sectorial and geographical distributions of greenhouse gas (GHG) emissions. Understanding these trends is central to the design of current and future climate change mitigation policies, requiring up-to-date methodologically robust emission inventories such as the Emissions Database for Global Atmospheric Research (EDGAR), the European Commission's in-house, independent global emission inventory. EDGAR is a key tool to track the evolution of GHG emissions and contributes to quantifying the global carbon budget, providing independent and systematically calculated emissions for all countries. According to the results of the EDGAR v.5.0 release, total anthropogenic global greenhouse gas emissions (excluding land use, land use change and forestry) were estimated at 49.1 Gt CO2eq in 2015, 50 % higher than in 1990, despite a monotonic decrease in GHG emissions per unit of economic output. Between 1990 and 2015, emissions from developed countries fell by 9%, while emissions from low to medium income countries increased by 130%, predominantly from 2000 onwards. The 27 Member States of the European Union and the United Kingdom led the pathway for emission reductions in industrialised economies whilst, in developing countries, the rise in emissions was driven by higher emissions in China, India, Brazil and nations in the South-East Asian region. This diversity of patterns shows how different patterns for GHG emissions are and the need for identifying regionally tailored emission reduction measures.